Edición de una invectiva inédita contra Quevedo: Respuesta al libro intitulado "Política de Dios" - Alonso Veloso, María José (El Colegio de México, 2023)
In October 1626, a fierce diatribe was written against Quevedo and his Politics of God, government of Christ, tyranny of Satan, a treatise pub-lished a few months earlier. The existence of the controversial text, which circulated in a handwritten and anonymous form, was only recently discov-ered. It is also known that this invective led Quevedo to revise his treatise and to offer a censored version of the same. The purpose of this article is to provide an edition of the full, unpublished text of the Response to the book entitled “Politics of God”.